Impact and Molecular Mechanism of Microplastics on Zebrafish in the Presence and Absence of Copper Nanoparticles - Gao, Ning; Huang, Zhihui; Xing, Jianing; Zhang, Siyi; Hou, Jing (Frontiers in Marine Science, 2021)
The adverse effects of microplastics (MPs) in aquatic environments have attracted increasing attention and posed health risks along with nanomaterials. Therefore, the toxic effects of polystyrene microplastics (PS-MPs) with different particle sizes (0.07, 0.7 and 7 μm) on zebrafish in the presence and absence of copper nanoparticles (Cu-NPs) were evaluated. The acute toxicity of MPs on zebrafish was 7 μm > 0.07 μm > 0.7 μm. Both 0.07 and 7 μm MPs acted on chromosomes and significantly affected cell cycle process by affecting palmitoyl hydrolase activity; while 0.7 μm MPs acted on extracellular space and significantly affected the activity of endopeptidase inhibitor to affect the cholesterol transport. And 0.07 and 7 μm MPs dominantly affected “cell cycle” pathway by inhibiting DNA replication, delaying the progression of S phase and G2/M phase, and affecting the accurate arrangement and separation of chromosomes; while the 0.7 μm MPs activated numerous platelets to aggregate and adhere in damaged parts, enhanced the coagulation function of platelets, and promoted the formation of fibrin clots, thus abnormally activating the “hemostasis” pathway. The presence of Cu-NPs significantly changed the toxicity-related pathways induced by 7 μm MPs from “cell cycle” into “hemostasis,” but not for the smaller-sized MPs (0.07 and 0.7 μm). The combined exposure of Cu-NPs and 7 μm MPs acted on the extracellular region and significantly affected cholesterol transport by affecting the activity of cholesterol transporters. This study provides theoretical insights for the health risks of MPs to aquatic species and even humans in the actual ecosystem.